Holes in the Glycan Shield of the Native HIV Envelope Are a Target of Trimer-Elicited Neutralizing Antibodies - Laura E. McCoy; Marit J. van Gils; Gabriel Ozorowski; Terrence Messmer; Bryan Briney; James E. Voss; Daniel W. Kulp; Matthew S. Macauley; Devin Sok; Matthias Pauthner; Sergey Menis; Christopher A. Cottrell; et al. (2016)
Highlights•HIV neutralizing antibodies were isolated from rabbits immunized with BG505 SOSIP.664•These antibodies target a hole in the glycan shield of BG505•Serum neutralization specificity maps to the same immunodominant glycan hole•Most HIV strains lack a conserved glycan site that could be a neutralization targetSummaryA major advance in the search for an HIV vaccine has been the development of a near-native Envelope trimer (BG505 SOSIP.664) that can induce robust autologous Tier 2 neutralization. Here, potently neutralizing monoclonal antibodies (nAbs) from rabbits immunized with BG505 SOSIP.664 are shown to recognize an immunodominant region of gp120 centered on residue 241. Residue 241 occupies a hole in the glycan defenses of the BG505 isolate, with fewer than 3% of global isolates lacking a glycan site at this position. However, at least one conserved glycan site is missing in 89% of viruses, suggesting the presence of glycan holes in most HIV isolates. Serum evidence is consistent with targeting of holes in natural infection. The immunogenic nature of breaches in the glycan shield has been under-appreciated in previous attempts to understand autologous neutralizing antibody responses and has important potential consequences for HIV vaccine design.Graphical abstract